Œdipe a Colone. Opéra en trois actes - Sacchini, Antonio 1730-1786; Guillard, Nicolas François 1752-1814 (Paris Imbault, 1787)
The premiere of Œdipe a Colone, intended to inaugurate the new theatre at Versailles, was not a success, possibly due to the quality of the performances, the staging or the acoustics. Queen Marie Antoinette promised Sacchini a better production at Fontainebleau in the autumn, but the "Affair of the Diamond Necklace" meant she was unable to have her wish. The news that the production was cancelled is said to have hastened the death of the already seriously ill composer on October 9, 1786. Œdipe was given a posthumous performance by the Paris Opera at the Théâtre de la Porte Saint-Martin on February 1, 1787. This time the audience was warmly appreciative and the opera became one of the most popular pieces in the repertoire for several decades, reaching a total of almost 600 performances by 1844.
Antonio Sacchini was a prolific opera composer who worked in Italy, London and Paris, where he became a favorite of Queen Marie Antoinette.
Imbault plate number 100, Imbault signature on title page
Ex libris Mlle Eugenie de Fontenelle (gilt lettering on cover); 'A l'enfant Jesus Rue St. Honoré au coin de celle des Prouvaries. DES LAURIERS Tient Magasin de Papiers et Fournit le Bureaux. A Paris.' (plate)
Green leather binding, with title and owner's name on cut-outs of red leather with gilt embossed lettering
Représenté, pour la premiere fois, devant leurs Majestés à Versailles le 4. Janvier 1786. et par l'Academie Royale de Musique le 1er Fevrier 1787.
Keywords: 18th Century (1701-1800); Opera; Mythology; Paris (France); Versailles (France); Fontainebleau (France)